Translational regenerative medicine - Atala, Anthony 1958-; Allickson, Julie G. (Elsevier/AP, 2015)
Translational Regenerative Medicine is a reference book that outlines the life cycle for effective implementation of discoveries in the dynamic field of regenerative medicine. By addressing science, technology, development, regulatory, manufacturing, intellectual property, investment, financial, and clinical aspects of the field, this work takes a holistic look at the translation of science and disseminates knowledge for practical use of regenerative medicine tools, therapeutics, and diagnostics